Acute pancreatitis as an uncommon complication of hydatid cyst of the liver: A case report and systematic literature review. (February 2021) - Ben Mahmoud, Ahmed; Atri, Souhaib; Rebai, Wael; Maghrebi, Houcine; Makni, Amine; Kacem, Montasser Jameleddine
Abstract: Hydatid disease is a major health problem worldwide. The liver is the most frequent location of hydatid disease. Acute pancreatitis secondary to liver hydatid cyst ruptured in the biliary tract is scarce and fewly described in literature. The management of this pancreatic complication of liver hydatid disease is challenging and includes a combination of surgical and endoscopic approaches. We report herein a rare case of hydatid cyst of the liver with cysto-biliary communication revealed by acute pancreatitis. A systematic literature review of similar cases reported was provided to compare surgical and endoscopic techniques. A thirty-year-old woman was referred to our emergency unit for acute pancreatitis. The CT-scan findings revealed a liver hydatid cyst ruptured in the biliary tract and daughter vesicles within were found, responsible for C-grade acute pancreatitis. We decided then to perform an emergency surgery through a bisoucostal incision. We performed a cholecystectomy and a peroperative cholangiogram that showed the communication between the cyst and left biliary tracts and the presence of daughter vesicle within the common bile duct. We conducted an exploration of the common bile duct with extraction of vesicle daughters. We left behind a T-tube in the common bile duct and we sutured the cysto-biliary fistula. Drainage was left in the remnant cavity after unroofing the cyst. Postoperative course was uneventful. Six months follow-up showed no recurrence. Cysto-biliary communication of liver hydatid disease revealed by acute pancreatitis is uncommon. We chose to perform emergency open surgery. However, through a systematic literature review, we noticed that endoscopic treatment is an efficient therapeutic and diagnostic tool to delay a morbid surgery of the liver and the common bile duct. Highlights: Acute pancreatitis revealed by liver hydatid cyst ruptured in the biliary tracts is a scarce condition. The management of this uncommon disease is challenging and includes a combination of surgical and endoscopic approaches. Endoscopic treatment is an interesting tool in acute phase and delay morbid open surgery. Open surgery is the standard treatment and remains the only procedure to eradicate the hydatid disease.